2014
DOI: 10.17827/aktd.84233
|View full text |Cite
|
Sign up to set email alerts
|

Kronik Böbrek Yetmezliğinde Tamamlayıcı ve Alternatif Tıp Yöntemleri

Abstract: Despite its long history, use of complementary and alternative medicine (CAM) methods has increased dramatically only after 1990s. Up to 57% of patients with chronic renal use CAM methods.These patienys use CAM methods to overcome hypertension, fatigue, constipation, leg edema, pain, cramps, anxiety, depression, sleep disorders, to cope with symptoms such as itching, to stop the progression of kidney disease and to improve their quality of life. Methods used are herbal products and food supplements, acupressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
0
0
7
Order By: Relevance
“…The frequency of AM/CM use was 52.7% in essential hypertension (17), 56.8% in chronic obstructive pulmonary disease (18), 48.8% in breast cancer (19), and 57% in chronic kidney failure (20). The frequency of AM/CM use in MS in our study was similar to frequencies reported in other chronic diseases.…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of AM/CM use was 52.7% in essential hypertension (17), 56.8% in chronic obstructive pulmonary disease (18), 48.8% in breast cancer (19), and 57% in chronic kidney failure (20). The frequency of AM/CM use in MS in our study was similar to frequencies reported in other chronic diseases.…”
Section: Discussionsupporting
confidence: 80%
“…Che-yi ve arkadaşları 40 hastaya bir ay boyunca haftada üç kez tek akupunktur noktasına Quchi (LI11) iğneleme tekniğini uygulamış ve akupunktur grubunun kaşıntı puanında anlamlı derecede azalma olduğunu belirlemişlerdir [26]. Diğer bir integratif yöntemlerden aromaterapiye ise KBY hastalarının sıklıkla başvurduğu bildirilmiştir [6]. Aromaterapi; genellikle bitkisel öz yağlar, solunum ve deri yoluyla uygulanmaktadır [5].…”
Section: Değerlendirme Ve Izlemunclassified
“…KBY'de kanda ürik asit, üre ve kreatinin gibi azotlu maddeler birikerek üremi tablosu gelişir. Üremi tablosu birçok sistem ve organın hasarına, yorgunluk, halsizlik, uyku sorunları, kansızlık, gastrit, iştahsızlık, yaralarda geç iyileşme, deride kuruluk ve kaşıntı gibi hastanın yaşam kalitesini olumsuz yönde etkileyen komplikasyonlara neden olabilir [3][4][5][6].…”
Section: Introductionunclassified
See 2 more Smart Citations